2022
DOI: 10.3389/fimmu.2022.881191
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Immune and Inflammatory Responses in Rheumatoid Arthritis

Abstract: PurposeRheumatoid arthritis (RA) is a disease associated with multiple factors. Epigenetics can affect gene expression without altering the DNA sequence. In this study, we aimed to comprehensively analyze epigenetic regulation in RA.MethodsUsing the Gene Expression Omnibus database, we identified a methylation chip, RNA-sequencing, and miRNA microarray for RA. First, we searched for DNA methylation, genes, and miRNAs associated with RA using differential analysis. Second, we determined the regulatory networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Several lines of evidence associated with our identified enriched genes support this hypothesis. For example, the products of the four most enriched candidate genes, AQP1, ABL2, CHD3, and RELN, participate in inflammatory activation, cell adhesion and migration, wound healing, and organ regeneration [36][37][38][39][40][41]. In addition, they play important roles in the nervous system and are associated with central and periphery neuropathies [39,[42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence associated with our identified enriched genes support this hypothesis. For example, the products of the four most enriched candidate genes, AQP1, ABL2, CHD3, and RELN, participate in inflammatory activation, cell adhesion and migration, wound healing, and organ regeneration [36][37][38][39][40][41]. In addition, they play important roles in the nervous system and are associated with central and periphery neuropathies [39,[42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K-Akt signalling pathway regulates the cellular inflammatory response, and hypermethylated-low expression genes were enriched in this pathway, which showed DNA methylation may activate the pathway and aggravate RA. Hypomethylated-high expression genes were also found to be affecting the T-cell receptor pathway, resulting in the pathogenesis of RA [6]. The differentially methylated regions identified above shed new light on epigenetic treatments.…”
Section: Rheumatoid Arthritismentioning
confidence: 94%
“…A recent study identified several differentially methylated genes and associated signaling pathways [6]. PI3K-Akt signalling pathway regulates the cellular inflammatory response, and hypermethylated-low expression genes were enriched in this pathway, which showed DNA methylation may activate the pathway and aggravate RA.…”
Section: Rheumatoid Arthritismentioning
confidence: 97%
See 1 more Smart Citation
“…Millimeter wave (millimeter wave) is a kind of electromagnetic wave, its frequency band is not too precise definition, usually the wavelength of 1 ~ 10 mm, the frequency of 30 ~ 300 GHz electromagnetic wave is called millimeter wave, it is located in the wavelength range of microwave and far infrared wave overlap, both the characteristics of the two wave spectrum, the wavelength of the commonly used clinical treatment instrument is 8mm, the frequency of 37.5 GHz. Millimeter wave is a series of non-thermal biological effects caused by electromagnetic radiation to regulate cell metabolism, accelerate the repair of damaged tissues, effectively enhance microcirculation, improve blood perfusion, reduce edema in the operating area and relieve pain [51][52]. It has been used in the treatment of rheumatoid arthritis, knee pain, low back pain, headache and other painful conditions [52][53][54][55].…”
Section: Millimeter Wavesmentioning
confidence: 99%